Transformation Of Village Services Through Implementation of The Village Information System Web - Rismawati Rismawati; Miftakul Huda Huda (Universitas INABA, 2023)
Public services are one of the important tasks that cannot be ignored by local governments because if the service component experiences stagnation, it is almost certain that all sectors will impact congestion. Therefore, there needs to be good planning and even needs to be formulated service standards for the community in accordance with the authority given by central government to local government. By providing positive and quality services, empirically, on the one hand, it will create satisfaction, happiness, and welfare of the community, which in turn will be able to realize village development goals. The purpose of this community service is to find out the role of service through Service Transformation by Implementing the Village Information System Web towards the people of Cipayung village. In community service in Cipayung village, East Cikarang district, there are 4 methods used, namely observation, interviews, training, and counseling. Implementation of the Cipayung Village Information System Web plays a role in informing the existence of Cipayung village, improving online village services, inputting data digitally, providing information on the wall, and having a neat file storage layout